PENGATURAN HUKUM PENGELOLAAN PERTAMBANGAN BATUBARA SECARA BERKELANJUTAN DI KOTA SAMARINDA - Siti Kotijah (Yuridika, 2012)
Legal arrangements on sustainable management of Coal Mining in Samarinda, have many rules violation in the provisions of the Mineral and Coal Act number 4 of 2009 particularly on Mining Management section. These predicaments caused profound consern due to the importance of natural resources preservation for sustainable development for the next generations. Therefore, to manage the existing natural resources which is coal, a sustainable long term regulation is needed in order to gain maximum benefits from coal management. Then, the benefits not only enjoyed by the present generation but also by the future generations.Key word: Law, management, Coal Mining.